Therapeutic Potential of Astragaloside IV Against Adriamycin-Induced Renal Damage in Rats via Ferroptosis - Qin, Lu-Yun; Guan, Peng; Wang, Jian-Xin; Chen, Yu; Zhao, Ya-Shuo; Yang, Sheng-Chang; Guo, Ya-Jing; Wang, Na; Ji, En-Sheng (Frontiers in Pharmacology, 2022)
Adriamycin is often used in the treatment of cancer, but continuous administration of Adriamycin can cause kidney damage. The main component of astragaloside Ⅳ of Astragalus Root has a renal protective effect, but its protective mechanism in Adriamycin-induced renal injury is not clear. In the present study, we revealed that astragaloside Ⅳ alleviates the kidney injury induced by Adriamycin via inhibiting ferroptosis. The human proximal tubular epithelial cells (HK-2) and SD rats were used to reveal the protective role of ASIV on Adriamycin-induced renal injury. ASⅣ treatment alleviated the pathological alterations and improved the renal dysfunction in rats with renal injury caused by Adriamycin. Treatment of the HK-2 cells with fer-1 and Deferoxamine mesylate obviously decreased Adriamycin-induced ferroptosis. Furthermore, RSL3 partially inhibited the protective role of ASⅣ on Adriamycin-induced renal injury. And, we found that ASⅣ could restore the expression of p-PI3K, p-Akt and Nrf2 reduced by ADR. In terms of mechanism, PI3K inhibitor was used to detect the role of PI3K/Akt/Nrf2 pathway in protecting ADR-induced ferroptosis by ASⅣ. Moreover, ferroptosis was significantly inhibited by decreased lipid peroxidation and iron accumulation after ASⅣ treat in vivo and vitro. These results revealed that ASⅣ plays a protect role in rat kidney damage induced by Adriamycin, possibly by inhibiting ferroptosis.